Design of a dual-bed catalyst system with microporous carbons and urea-supported mesoporous carbons for highly effective removal of NOx at room temperature. Issue 33 (15th March 2016) - Li, Jun; Yin, Di; Long, Donghui; Wang, Jitong; Ling, Licheng; Qiao, Wenming
Abstract : A dual-bed catalyst system is designed for highly effective remove of NO x at room temperature, which consists of a microporous spherical activated carbon (SAC) layer and a urea-supported spherical mesoporous carbon (SMC) layer. Abstract : A dual-bed catalyst system is designed to remove NO x at room temperature, which consists of a microporous spherical activated carbon (SAC) layer and a urea-supported spherical mesoporous carbon (SMC) layer. The SAC layer, with plenty of narrow micropores acting as a nano-cage for NO adsorption, could improve the oxidation of NO into NO2, while the urea-supported SMC layer with large surface area could provide a sufficient channel for gas kinetic diffusion and a high gas/urea interfacial area for efficient NO2 reduction. A high stationary-state NO x conversion of 88% for 70 h is achieved through the dual-bed catalyst system with SAC and 100 wt% urea supported SMC as the catalyst. The selective catalytic reduction (SCR) activity could be improved by increasing the NO and O2 feed concentration, due to the enhanced oxidation of NO to NO2 . A low reaction temperature is beneficial for the SCR reaction because of the increased NO adsorption. Moreover, the apparent activation energies are calculated to be −16.8 kJ mol −1 for NO oxidation and 1.18 kJ mol −1 for NO2 –urea SCR, respectively. The result reveals that the adsorption of reactants on SAC is of key importance for NO oxidation, while the surface reaction of NO2 with urea could be the crucial step for the SCR reaction.